Simple Parameters from Complete Blood Count Predict In-Hospital Mortality in COVID-19. (13th May 2021) - Bellan, Mattia; Azzolina, Danila; Hayden, Eyal; Gaidano, Gianluca; Pirisi, Mario; Acquaviva, Antonio; Aimaretti, Gianluca; Aluffi Valletti, Paolo; Angilletta, Roberto; Arioli, Roberto; Avanzi, Gian Carlo; Avino, Gianluca; et al.
Abstract : Introduction . The clinical course of Coronavirus Disease 2019 (COVID-19) is highly heterogenous, ranging from asymptomatic to fatal forms. The identification of clinical and laboratory predictors of poor prognosis may assist clinicians in monitoring strategies and therapeutic decisions. Materials and Methods . In this study, we retrospectively assessed the prognostic value of a simple tool, the complete blood count, on a cohort of 664 patients (F 260; 39%, median age 70 (56-81) years) hospitalized for COVID-19 in Northern Italy. We collected demographic data along with complete blood cell count; moreover, the outcome of the hospital in-stay was recorded. Results . At data cut-off, 221/664 patients (33.3%) had died and 453/664 (66.7%) had been discharged. Red cell distribution width (RDW) (χ 2 10.4; p < 0.001 ), neutrophil-to-lymphocyte (NL) ratio (χ 2 7.6; p = 0.006 ), and platelet count (χ 2 5.39; p = 0.02 ), along with age (χ 2 87.6; p < 0.001 ) and gender (χ 2 17.3; p < 0.001 ), accurately predicted in-hospital mortality. Hemoglobin levels were not associated with mortality. We also identified the best cut-off for mortality prediction: a NL ratio > 4.68 was characterized by an odds ratio for in-hospital mortality OR = 3.40 (2.40-4.82), while the OR for a RDW > 13.7 % was 4.09 (2.87-5.83); a platelet count > 166, 000 / μ L was, conversely, protective (OR: 0.45 (0.32-0.63)). Conclusion. Our findings arise the opportunity of stratifying COVID-19 severity according to simple lab parameters, which may drive clinical decisions about monitoring and treatment.